Growth Performance of Scalloped Spiny Lobster (Panulirus homarus) Given Artificial Feed Based on Chicken Eggs Hatching Waste - Natasya Cahya Okta; Fariq Azhar; Andre Rachmat Scabra; Abdul Syukur; Muhammad Amin; Faturrahman Faturrahman (Jurnal Kelautan Tropis, 2023)
The availability of cheap and high nutritional value artificial feed is a prerequisite for the sustainability of lobster cultivation. In this study, the lobster feed formula was made based on chicken egg hatching waste and maggot flour. The purpose of this study was to determine the performance of scalloped spiny lobsters with artificial feed treatment P1 (70% fish meal + 0% hatching waste), P2 treatment (50% fishmeal + 20% hatching waste), P3 treatment (30% fishmeal + 40% hatching waste), and P4 treatment (10% fishmeal + 60% hatchery waste). This study used lobster seedlings with a size of 1.5 - 3.5 cm which were kept for 60 days. Lobster performance is measured based on body weight, body length, growth rate, feed conversion, molting and lobster dilution rate. The data were analyzed descriptively by presenting mean, standard deviation, and statistical analysis using Duncan's advanced test. The results of the lobster performance study based on absolute length and weight in the P1 treatment were obtained 1.22±0.05 and 1.03±0.21; on P2 treatment obtained 1.31±0.16 and 1.16±0.09; P3 treatment obtained 1.37±0.37 and 1.47±0.13; and P4 treatment obtained 0.82±0.18 and 0.9±0.22. The calculation of the specific growth rate in the P1 treatment was obtained 0.56±0.09, the P2 treatment was obtained 0.69±0.21, the P3 treatment was obtained 0.73±0.16, and the P4 treatment was obtained 0.56±0.24. The ratio of feed conversion and lobster dilution shows a tendency to decrease as the concentration of chicken hatching waste increases. The growth performance of scalloped spiny lobsters fed with chicken egg hatching waste-based feed is quite good up to a concentration of 40% and if more than that will reduce the growth performance of lobsters.